Insecticidal effect of Eucalyptus globulus and Rosmarinus officinalis essential oils on a stored food pest Ephestia kuehniella (Lepidoptera, Pyralidea): Insecticidal effect of Eucalyptus and Rosmarinus essential oils - Rekioua, Naouel; Boumendjel, Mahieddine; Taibi, Faiza; Samar, Mohamed Faouzi; Jemaa, Jouda Mediouni Ben; Benaliouch, Fouzia; Negro, Carmine; Nicoli, Francesca; De Bellis, Luigi; Boushih, Emna; Haouel, Soumaya (Cellular and Molecular Biology, 2022)
For the purpose of evaluating the local heritage of eastern Numidia, an ethnobotanical survey was conducted on a population located in the province (department) of El-Tarf (North-East of Algeria) on a frequency of use of two plants known in traditional health; Eucalyptus globulus (Myrtaceae) and Rosmarinus officinalis (Lamiaceae). After processing data, our results show a female dominance when using these plants on a fairly advanced age group (40 to 60 years old). These plants are used by the people at their fresh state and deem the leaf as the most used part for therapeutic and cosmetic purposes. Furthermore, steam baths and infusion remain the most widespread preparation methods. Most consumers use these plants to treat influenza, respiratory illnesses as well as diseases of the digestive tract. GC-MS of essential oils extracted from the plants studied disclose a dominance of the alcohols portrayed by the monoterpenes (42.73%), sesquiterpenes (32.6%) and oxides (10.48%) in E. globulus. Data also indicate a high content of oxides (38.11%) monoterpene alcohols (20.43%) and monoterpenes (19.70%) in R.officinalis. Toxicological contact tests were achieved on a store-products pest Ephestia kuehniella. The test results were assessed with E.globulus (LC50=0.013; LC95=0.081 µl/cm2) and R.officinalis (LC50=0.011; LC95=0.059 µl/cm2). The lethal time changes according to the dose used and the tested plant. In E.globulus, we observe (concentration: 0.005 µl/cm2; LT50=56.2 h), (Concentration: 0.01 µl/cm2; LT50=49.53h) and (Concentration: 0.04µl/cm2; LT50=20.93h). Whereas in R.officinalis, we recorded (Concentration: 0.005 µl/cm2; LT50=55.7h), (Concentration: 0.01µl/cm2; LT50=54.99 h) and (Concentration: 0.04µl/cm2; LT50=29.13 h). The bioinsecticide has also been administered by fumigation and underpins toxicity by the reduction of adults longevity in E.kuehniella with R.officinalis (LC50=4.03 µl/l air; LC95=14.73 µl/l air) and E.globulus (LC50=7.76 µl/lair; LC95=21.23 µl/l air). In addition, the tested plants show an outstanding repellent effect as long as E.globulus and R.officinalis essential oils respectively demonstrate a slightly repellent power at 42.22% (RD50=0.09 µl/cm2 ; RD95=0.24 µl/cm2) and repellent at 60.00% (RD50=0.06 µl/cm2 ; RD95= 0.35 µl/cm2) towards E.kuehniella adults. The plant resources represent a genuine reserve of bioactive molecules, which can create solutions to sustainable development issues. These plants might be the source of new molecules of combat against some pests in order to protect human health and safeguard the environment.